Ministry of Agriculture, Livestock, Fisheries and Cooperatives State Department of Livestock - Kenya Livestock Breeds Catalogue - AU-IBAR, Ministry of Agriculture, Livestock, Fisheries and Cooperatives State Department of Livestock (AU-IBAR, 2019)
This catalogue provides consolidated information on livestock diversity available in Kenya, including their distribution, utilization, current status and associated risks.
Kenya Livestock Breeds Catalogue
This is the first National Livestock Breeds Catalogue for Kenya. It has been developed through a consultative process involving key stakeholders in the livestock industry. It highlights the diversity of animal genetic resources (AnGR) in Kenya covering the various species and breeds that are used for food and agriculture. They include cattle, goats, sheep, camel, poultry, pigs, donkeys, rabbits and honey bees.
Keywords: Livestock Development; Animal Genetic Resources; Animal Health; Animal Production